2016
DOI: 10.1007/978-3-319-43681-4_9
|View full text |Cite
|
Sign up to set email alerts
|

The Gene Family-Free Median of Three

Abstract: Background:The gene family-free framework for comparative genomics aims at providing methods for gene order analysis that do not require prior gene family assignment, but work directly on a sequence similarity graph. We study two problems related to the breakpoint median of three genomes, which asks for the construction of a fourth genome that minimizes the sum of breakpoint distances to the input genomes.Methods: We present a model for constructing a median of three genomes in this family-free setting, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…However, in 2009, Tannier, Zheng and Sankoff proved that computing a median gene order that is allowed to contain an arbitrary mixture of linear and circular chromosomes was tractable in the breakpoint distance model, by using a reduction to the problem of computing a Maximum Weight Matching (MWM) [22]. This tractability result, the first of its kind in genome rearrangements, renewed the interest in gene order median problems, although most of the following work presented intractability results, even on variations of the breakpoint distance [5,9,14]. A notable exception was the Single-Cut-or-Join (SCJ) distance, introduced by Feijão and Meidanis [11], where it was shown that both the SCJ median problem and the SCJ SPP are tractable.…”
Section: Introductionmentioning
confidence: 98%
“…However, in 2009, Tannier, Zheng and Sankoff proved that computing a median gene order that is allowed to contain an arbitrary mixture of linear and circular chromosomes was tractable in the breakpoint distance model, by using a reduction to the problem of computing a Maximum Weight Matching (MWM) [22]. This tractability result, the first of its kind in genome rearrangements, renewed the interest in gene order median problems, although most of the following work presented intractability results, even on variations of the breakpoint distance [5,9,14]. A notable exception was the Single-Cut-or-Join (SCJ) distance, introduced by Feijão and Meidanis [11], where it was shown that both the SCJ median problem and the SCJ SPP are tractable.…”
Section: Introductionmentioning
confidence: 98%